Addressing gender in agricultural research for development in the face of a changing climate: where are we and where should we be going? - Kristjanson, Patricia M.; Bryan, Elizabeth; Bernier, Quinn; Twyman, Jennifer; Meinzen-Dick, Ruth S.; Kieran, Caitlin; Ringler, Claudia; Jost, Christine; Doss, Cheryl (Informa UK Limited, 2017)
Agricultural development efforts that do not address persistent gender gaps miss opportunities for greater impact. This synthesis reflects on key findings from integrated quantitative and qualitative analyses at the nexus of gender, agricultural development, and climate change. Linked farm household-, intrahousehold-, community-, and institutional-level data highlight significant and nuanced gender differences in adaptive capacity of individuals and communities to respond to climate change. The gender gap is also substantial in exposure to climate change and its impacts, and uptake of new practices that lower vulnerability. Women in agriculture will remain largely neglected by information and service providers unless their differing needs, access to, and control over resources are considered at policy and project design stage. Yet clear guidelines for addressing the needs of both men and women in different environments and agricultural systems are still lacking. Participatory ‘action research’ approaches with a focus on co-learning, and using innovative cell phone or social media-based approaches offer exciting new opportunities. Agricultural development decision-makers and project designers need to ‘design with gender in mind’. Equipping them with tools and knowledge of innovative gender-transformative practices and intervention options and creating accountability for serving women and men will be key.